Beverage quality and safety - Foster, Tammy (CRC Press LLC, 2011)
Based on an IFT short course, Beverage Quality and Safety offers information on the latest beverage industry trends related to products, processing, and packaging technologies - including new generation nutraceutical beverages. It also covers important regulatory issues, including federal regulations on HACCP.